(untitled) (Research, Society and Development, 2020)
The objective of this study was to identify the works published in the national literature that describe their experiences in the systematization of Nursing Care through the execution of the Nursing Process in the care provided and the nursing theory used to support the operationalization of the Nursing Process. An exploratory, descriptive study with a quantitative approach was carried out, using two descriptors and a term from the Virtual Health Library, in an associated way, in the LILACS, BDENF and SCIELO databases, from 2009 to 2019. After previous analysis of the abstracts and methodology, the case report works were included in the research, which depicted in their main subject the descriptive and term, "Nursing Process", "Nursing Theory" and "Nursing Systematization". Nine studies were selected to elaborate the research. The theories most used by the authors were Wanda Aguiar Horta’s theory of basic human needs and Dorothea Elizabeth Orem’s theory of self-care. There was a consensus regarding the importance of carrying out the nursing process in nursing care, which needs to be definitively incorporated into nursing care. Despite the authors’ conformity with the importance of systematizing nursing care and the nursing process, the need for awareness and training for professionals on the topic was raised.